A scoring system based on clinical features for the prediction of sporadic renal angiomyolipoma rupture and hemorrhage. Issue 20 (15th May 2020) - Xu, Xiao-feng; Hu, Xian-hui; Zuo, Qi-ming; Zhang, Jiao; Xu, Hao-yu; Zhang, Yao
Abstract : Abstract: The purpose of this study is to analyze the risk factors of sporadic renal hamartoma and establish a risk scoring system, and to intervene in patients with high-risk sporadic renal hamartoma who are prone to rupture and bleeding as soon as possible. Retrospective univariate and multivariate logistic analyzes were conducted for clinical data of 332 sporadic renal hamartoma patients to screen out independent risk factors of tumor rupture. Score of each independent risk factor was calculated. (Calculation formula: the risk coefficient of each factor = the beta regression coefficient of each factor/the minimum value of the beta regression coefficient of all factors, the value of the smallest beta regression coefficient corresponding to all the factors was assigned 1 point. The score of each factor was equal to the risk coefficient of each variable was taken as an integer value by rounding.) The total score was equal to the sum of all factors. Then the area under the receiver operating characteristics (AUC) curve was compared between high risk factors and scoring system. Finally, the scoring system was evaluated by the area under the curve (AUC) and the Hosmer–Lemeshow method in an independent cohort of 130 patients.Factors such as symptoms at presentation, tumor size, tumor blood supply, and tumor growth pattern were significant predictors of sporadic renal angiomyolipoma rupture in both the univariate and multivariate analyses; these predictors were included in the scoring system to predict sporadic renal angiomyolipoma rupture. There were no significant differences in AUCs between high risk factors and scoring system (z = 0.6434, P = .583, AUC = 0.913, and 0.903 for high risk factors and scoring system, respectively). The sporadic renal angiomyolipoma patients who scored >6 points were prone to rupture. AUROC of the scoring system in the validation set was 0.854(95%CI:0.779, 0.928). Using the Hosmer–Lemeshow method, the value of X 2 was 2.916, P = .893, suggesting the scoring system fitted well. A scoring system based on clinical features is simple and effective in predicting sporadic angiolipoma rupture and hemorrhage. When the score is higher than 6 points, the probability of hamartoma rupture and hemorrhage is significantly increased and early intervention is needed.